THE EFFECTIVENESS OF GRAMMAR CORRECTION TO IMPROVE STUDENTS’ WRITING - Hartono Hartono (Dinamika Bahasa dan Budaya, 2011)
There has been a hot debate concerning the effectiveness of feedback provision especially grammatical feedbacks in second language writing.  The proponents of feedback provision argue that it can help students recognize their linguistic shortcomings.  If a teacher points out to a student a grammatical error he has made, and provides -indirectly or directly- the correct form, the student will then understand the mistake he has made, learn from it, and his ability to write accurately will improve.  The opponents, on the other side, argue that the practice is ineffective and harmful and that it should be abandoned.   It make no difference who the students are, how many mistakes are corrected, which mistakes are corrected, how detailed the comments are, or in what form they are presented, the corrections have no effect.  This research was aimed at finding out the effectiveness of feedback from the perspective of the students and the pre and post writing tasks.  Forty students participated as respondents.  They were the students of Writing 4 course at College of Language of Sultan Agung Islamic University.  The participants in the research wrote essays and the teacher provided feedbacks for the grammatical errors found in the essays. At the end of the experiment, questionnaire of Likert-scale type inquiring their perception about the provision grammatical feedbacks were distributed. The data were analyzed descriptively. Their pre and post task writing scores were also compared statistically.   Keywords: grammatical feedback, effective, second language writing